Introducing CAPAB(L)E: A Learning Model to Promote Prospective Biology Teacher’s Entrepreneurship Skills - B. Supriatno; D. Kusumawaty; T. E. Tallei; T. B. Emran; T. Suwandi (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Biology is one of the fields of study that has a lot of scopes that have the potential to be directed to the entrepreneurship aspect. Currently, there is no report on a particular learning model that prepares prospective teachers to design and implement businesses related to the use of biological principles, processes, and products. This study aims to develop and validate an entrepreneur-oriented learning model of biology in higher education, later known as CAPAB(L)E. CAPAB(L)E, stands for Characterizing, Analyzing, Prototyping, Assessing, Building up, and Exposing, a bioentrepreneurship learning model to promote biology education students’ entrepreneurial skills was successfully designed through this research. This design-based research (DBR) used the ADDIE model, which consisted of five stages, namely: analysis, design, development, implementation, and evaluation. The logical validation sheet consisted of six objective items with four Likert scales and an open question regarding recommendations for improving the developed learning model filled by two validators or experts (a lecturer in biology learning design and a lecturer in entrepreneurship). In addition, to obtain an overview of students’ perceptions of the CAPAB(L)E learning model, a questionnaire was used containing six items of Likert Scale 4-level statements and an open question about skills that were most trained during learning. Research data were analyzed descriptively. The results of the logical validation of the hypothetical model of CAPAB(L)E bioentrepreneurship learning model indicate that the learning model is valid and can be implemented, with a score of 81,25%. The students’ perceptions are generally positive on the structure and content of the material. Students suggest using teamwork strategies in planning and implementing student businesses. Based on this research results, it is necessary to carry out further research to determine the effectiveness of CAPAB(L)E bioentrepreneurship learning on students’ skills, knowledge, and attitudes toward entrepreneurship.